Reduction possibilities of the production costs of green electricity by using waste heat - Barta-Juhász, Ilona (Acta Agraria Debreceniensis, 2014)
In my study, I examine the possibility of the reduction of green electric power’s gross production cost. My research topic may have wider considerations, since in the case of CHP technology the utilization of by-product thermal energy is not possible, and the whole production cost devolves upon green electric power. I introduce five options for the use of the heat energy, based on national and international literature and in-depth interviews.From the aspect of efficiency, it can be stated that as alternatives, beer production and desiccation may be mentioned, since these two models were appropriate for the utilization of the total quantity of waste heat, and in the given circumstances the lowest reduction of green electric power’s production costs was achieved in these cases utmost.